AN EMPIRICAL STUDY ON STRESS MANAGEMENT IN INFORMATION TECHNOLOGY INDUSTRY IN INDIA - Sharma, Dr Neha; Uniyal, Dr Mahesh; Fernandes, Prof. Sharmila; Basha, Prof. Mahabub (The journal of contemporary issues in business and government, 2022)
The employees of various organizations undergo lot of hardships and all sorts of pressure in work places during their work tenure. And especially employees working in IT companies have to spend time under heavy pressure of conflicting demands and work situations. They perform managerial functions under very compelling situations. This in turn leads to anxiety and stress. It is evident that challenges are posed by the changing business scenario, which forces upon the IT employees to perform their task under compelling situations. Information Technology professionals need to take responsibility for maintaining the necessary balance in their lives by addressing these workplace stressors. Once the stressors are identified by an individual, a commitment must be made to work on easing this stress. Generally, Information Technology employees are found to have various causes of stress like, heavy workload and its concomitant time pressures and unrealistic deadlines; what must be accomplished on the job and what the manager would like the employees to accomplish; the general organizational political climate; and lack of feedback on job performance.